Pengujian Keselamatan Thermal pada Battery Pack Sepeda Motor Listrik Berdasarkan Regulasi UN R-136 - Wikarta, Alief; Yuniarto, M. Nur; Sidharta, Indra (Jurnal Rekayasa Mesin, 2020)
The electric-motorcycle is one of the promising technology that can improve environmental quality as well as reduce dependency on oil imports in Indonesia. The major challenge of electric-motorcycle implementation is the safety of the lithium-ion battery pack. This research aims to ascertain the over-temperature protection, and also to carry out shock & cycling test for the battery thermal safety. The testing procedures and apparatus comply with the United Nations Regulation No 136 (UN R-136), namely a temperature humidity chamber, a battery load unit, a blower, and a charger. The first step is the designing and prototyping of the battery pack with 100 V and 30 Ah, which contains a module of cells, Battery Management System (BMS), wiring, isolator, socket, and aluminum casing. The second step is the battery thermal safety test. The results showed that the battery pack satisfied the acceptance criteria, with evidence of no electrolyte leakage, rupture, fire, and explosion during and after testing. Result of over-temperature protection, BMS can cut-off the discharge rate at a temperature of 45.89°C. Meanwhile, for thermal shock & cycling tests, the battery pack did not fail when the temperature changes from 59.72°C and -40.25°C for 60 hours.